If you mean the straight line formula of: y = mx+b
Then: 2x-3y-6 = 0 or y = 2/3 x -2 so m=2/3 and b=-2
If you mean that 2x-3y = -6 , then y = 2/3 x + 2 so m=2/3 and b= +2
Chat with our AI personalities
Convert the equation into y = mx + b form: 2x + 3y = 6 -2x -2x 3y = 6 - 2x Divide both sides by 3: y = 2- 2/3x If we move the terms around to put in in y = mx + b: y = -2/3x + 2 m is the slope, so the slope is -2/3
Convert the equation into the form y = mx + c, where m is the slope (and c is the y intercept) 2x + 3y = 18 3y = -2x + 18 y = -2/3x + 6 Therefore the slope is -2/3.
2x - 3y = 62x = 3y + 63y = 2x - 6y = (2x - 6)/3y = (2/3)x - 2
If you mean: 2x+3y = 6 then it is 2x+3y = 11
y = 4, x = 6